Plastid Class I and Cytosol Class II Aldolase of Euglena gracilis (Purification and Characterization). - Pelzer-Reith, B. (1994)
The plastidic class I and cytosolic class II aldolases of Euglena gracilis have been purified to apparent homogeneity. In autotrophically grown cells, up to 81% of the total activity is due to class I activity, whereas in heterotrophically grown cells, it is only 7%. The class I aldolase has been purified to a specific activity of 20 units/mg protein by anion-exchange chromatography, affinity chromatography, and gel filtration. The native enzyme (molecular mass 160 kD) consisted of four identical subunits of 40 kD. The class II aldolase was purified to a specific activity of 21 units/mg by (NH4)2SO4 fractionation, anion-exchange chromatography, chromatography on hydroxylapatite, and gel filtration. The native enzyme (molecular mass 80 kD) consisted of two identical subunits of 38 kD. The Km (fructose-1,6-bisphosphate) values were 12 [mu]M for the class I enzyme and 175 [mu]M for the class II enzyme. The class II aldolase was inhibited by 1 mM ethylenediaminetetraacetate (EDTA), 0.8 mM cysteine, 0.5 mM Zn2+, or 0.5 mM Cu2+. Na+, K+, Rb+, and NH4+ (but not Li+ or Cs+) enhanced the activity up to 7-fold. After inactivation by EDTA, the activity could be partially restored by Mn2+, Cu2+, or Co2+. A subclassification of class II aldolases is proposed based on (a) activation/inhibition by Cys and (b) activation or not by divalent ions.